Influence of fruit and vegetable intake on satiety and energy intake: a review - Bibi Nabihah Abdul Hakim,; Hanis Mastura Yahya,; Suzana Shahar,; Zahara Abdul Manaf, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Fruit and vegetable are the natural foods that contained various nutrients vital for good health and help in weight loss by suppressing an individual’s appetite. Therefore, this review aimed to investigate the acute effect of fruit and vegetable intake on satiety and energy intake. We included randomized controlled trial or experimental designs measuring fruit and/or vegetable intake on satiety using subjective appetite rating and appetite related hormone and energy intake among healthy adults, published in English-language. The use of extract, powder form or concentrated fruit and/or vegetable and animal study were excluded. Twelve studies were identified from Pubmed, Science Direct and Cochrane from the year 1995 to August 2017, consists of six studies on fruit and six studies on vegetable. This review discussed the preload of fruit and vegetable in promoting satiety and reducing the energy intake. Manipulating energy density rather than portion size was effective in reducing total energy intake and promotes satiety. Fruit and vegetable in solid form had a greater satiety effect and significantly reduce energy intake compared to liquid or pureed form. The variation in time interval between fruit and/or vegetable intake and the test meal may also account a significant effect on satiety up to 2 h and diminished 3 h onward. The satiety effect of fruit and vegetable would be beneficial in body weight management.